2003
DOI: 10.1364/oe.11.001237
|View full text |Cite
|
Sign up to set email alerts
|

Aging of porous silicon and the origin of blue shift

Abstract: Aging effects of porous silicon (PS) and the origin of blue shift are investigated. Photoluminescence (PL) measurements of the PS prepared with HF-EtOH solution showed a 210 meV blue shift after 1.5 months. It is found from deconvolution of the PL spectra that this shift is not fully related to the quantum confinement (QC) effect. For stable PS formation, a HFEtOH-H2O2 solution is used. A stable luminescence at 2.01 eV with a Gaussian distribution is obtained when the samples are kept in H2O2 for 45 min after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…a native oxide layer forms on the surface of pores. Due to the ageing effect, the structural (Astrova et al 2002), electrical and optical properties (Karacali et al, 2003) of PS showed continuous change with the time. The growth of the native oxide was completed approximately after one year (Petrova, et al, 2000).…”
Section: Surface Stabilization Of Nps By Different Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…a native oxide layer forms on the surface of pores. Due to the ageing effect, the structural (Astrova et al 2002), electrical and optical properties (Karacali et al, 2003) of PS showed continuous change with the time. The growth of the native oxide was completed approximately after one year (Petrova, et al, 2000).…”
Section: Surface Stabilization Of Nps By Different Methodsmentioning
confidence: 99%
“…Illumination and increased temperature enhance the oxidation reaction rate. A blue shift in the luminescence spectra occurs after oxidation of the surface (Hossain et al 2000, Karacali et al 2003. It also affects the electrical conductivity and the optical properties of the porous layer (Astrova et al 1999).…”
Section: Chemical Properties Of Porous Siliconmentioning
confidence: 99%
“…The huge numbers of surface states, interface states, and volume traps, of the order of 10 15 cm -3 eV -1 are present in the quasi-Fermi level of PSi layer (Matsumoto et al 1998), mainly originated from its nanostructure. These defect states are responsible for the creation of the recombination centers, the slow uncontrolled surface oxidation (Beckmann 1965;Petrova et al 2000;Astrova et al 2002;Karacali et al 2003), Fermi-level pinning Kanungo et al 2009a), and hinder the electrical response of the PSi-Si interface. Therefore, the surface passivation of PSi is an important step to make a stable device for practical application.…”
Section: Aging Effect Of M-psi Contactsmentioning
confidence: 99%
“…Thus, studies on the light emitting feature of porous silicon (PS) structures have tremendously intensified since the discovery of visible luminescence at room temperature [1]. The luminescence spreading from near infrared throughout the visible region is known to originate from the monocrystalline skeleton [2,3] and is affected by aging of dangling bonds on the PS surface [4,5]. Obtaining a stable photoluminescence (PL) spectrum is crucial in optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining a stable photoluminescence (PL) spectrum is crucial in optoelectronic applications. Studies have been done to obtain a stable radiation of unprocessed PS structures, because PL spectrum shifts by time [5][6][7][8][9]. To obtain a similar radiation property for processed PS structures, electrochemical or thermal oxidation was carried out on PS surface in some studies [10,11], while carbonization was applied in the others [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%